2022
DOI: 10.52312/jdrs.2022.445
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of osteoarthritic changes, loss of cervical lordosis, and disc space narrowing on cervical radiographs with deep learning methods

Abstract: Although the cervical spine supports the head, it has quite functional features such as flexion, extension, lateral flexion, and rotation. Due to this wide range of motion, there is a susceptibility to trauma and degenerative changes. Neck pain due to cervical spine problems is a very common medical problem in the adult population. Cervical strain, cervical spondylosis, and discopathies are common causes of mechanical neck pain. Apart from these, traumas, tumors and reflected pain are also important causes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…For localization tasks, DSNT was used as the top level. Maraş et al 9 compared different deep convolutional neural networks (DCNN) in terms of their performance for vertebral segmentation of the X-ray images of the cervical spine. The pre-trained networks used in this work were VGG-16, VGG-19, Resnet-101 and DenseNet-201, with the overall achieved classification accuracy of 93.9, 91.8, 89.8 and 85.7%, respectively.…”
Section: Related Workmentioning
confidence: 99%
“…For localization tasks, DSNT was used as the top level. Maraş et al 9 compared different deep convolutional neural networks (DCNN) in terms of their performance for vertebral segmentation of the X-ray images of the cervical spine. The pre-trained networks used in this work were VGG-16, VGG-19, Resnet-101 and DenseNet-201, with the overall achieved classification accuracy of 93.9, 91.8, 89.8 and 85.7%, respectively.…”
Section: Related Workmentioning
confidence: 99%
“…The CNN is an artificial neural network (ANN) algorithm that applies multilayer neural network structure. [2] Deep learning may be a beneficial assistant in the detection of bone fractures, for the evaluation of…”
Section: Reviewmentioning
confidence: 99%
“…President, Turkish Joint Diseases Foundation, Ankara, Türkiye cervical arthrosis and robotic joint arthroplasty. [1][2][3] However, the public unawareness of the doubtful outcome superiority associated with robotic-assisted orthopedic surgery may contribute to misinformed decisions in some patients. For a better evaluation of the utility of robotic joint arthroplasty, further well-designed, prospective, controlled studies with long-term follow-up would be helpful.…”
Section: O şAhap Atik Mdmentioning
confidence: 99%
See 1 more Smart Citation
“…Alexnet, VGG-16, GoogLeNet, ResNet-50, and Squeezenet are the most well-known transfer learning methods. [6][7][8] Research has shown that deep learning methods are very effective in medical image analysis by saving time and computational costs. [5] In deep learning methods, the working mechanisms of neurons in the human brain are imitated, together with simultaneous utilization of the processing power of the computer.…”
mentioning
confidence: 99%